Pengaruh Motivasi Dan Disiplin Terhadap Kepuasan Dan Kinerja Guru Dan Tenaga Kependidikan (Studi Empiris Pada SMK Muh 2 Sukoharjo Kabupaten Sukoharjo) - Hamdani, Anwar; Mualim, Hadi (STIE AUB Surakarta)
This study aims to determine the effect of work motivation and discipline to the performance of teachers and employees with job satisfication as an intervening variable (empirical studies at SMK Muh 2 Sukoharjo Sukoharjo District)Keywords: Work motivation,job discipline,job satisfication